Pengembangan Media Komik Digital pada Pembelajaran Sejarah Kelas X SMA Negeri 2 Tilatang Kamang pada Peradaban Awal di Kepulauan Indonesia - Randa Ferdiansyah; Zulfa Zulfa; Meldawati Meldawati (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to overcome the lack of enthusiasm for learning in history subjects at SMA 2 Negeri Tilatang Kamang. The focusis evaluating the validity and quality of digital comic media as a history learning tool in class X E.2. The method used is research and development with a 4-D model (Define, Design, Development, Disseminate). The research participants were 22 students of class X E.2 who were studying history. The results showed that digital comic media had very good validity with an average score of 83.4%, including material aspects (91.6%), language eligibility (80.3%), and media eligibility (78.4%). The practicality of the media is positively evaluated by the teacher with a score of 86.8% and by students with a score of 88.16%, indicating that this media is very practical in the learning process. In conclusion, this digital comic media has high validity, good practicality, and the potential to increase students' learning motivation in history subjects. This research produces innovative and effective learning tools to overcome challenges in learning history.